nfrastructure as a determining factor in the professional training of students of Agroindustrial Engineering, Food Industries and Industrial of the Private University of Tacna - Ruffrán Sarmiento, Edda Milagros (2014)
At present it is very important that all higher education institutions have quality physical infrastructure, complying with standards of fairness, security and where the regulations apply as well to ensure quality education and training. Objective: The objective of the research is to formulate and develop the project Architectural Infrastructure for the careers of Agroindustrial Engineering, Industrial Engineering and Engineering Food Industry to meet the academic needs with the aim of making quality vocational training while in a decisive national and international accreditation in the Private University of Tacna factor. Method: The methodology used was descriptive research used in step information and data collection to get a diagnosis and propose experimental allow adequate infrastructure. Result: As a result of the research project develops a aquitectonico considering their respective merits. Conclusions: General strategy for the project is aimed at initiating and supporting a proposed educational quality infrastructure to solve the problems of lack thereof in the Faculty of Engineering - UPT